Knowledge, Attitude, and Practice Regarding Pharmacovigilance and Barriers to Reporting Adverse Drug Reactions Among the General Population in Saudi Arabia - Alshehri H; Alharbi A; Alqethami N; Alnuhait M; Alshammari A; Alotaibi AS (Dove Medical Press, 2024)
Hind Alshehri,1 Adnan Alharbi,1 Noof Alqethami,2 Mohammed Alnuhait,1 Abdullah Alshammari,1 Abdulmalik S Alotaibi1 1Pharmaceutical Practices Department, College of Pharmacy, Umm Al-Qura University, Makkah, Saudi Arabia; 2Clinical Pharmacy Department, Taif Health Cluster, King Faisal Medical Complex, Taif, Saudi ArabiaCorrespondence: Abdulmalik S Alotaibi, Email assalotaibi@uqu.edu.saBackground: Pharmacovigilance (PV) is an essential part of the healthcare system's framework. In Saudi Arabia, pharmacovigilance is still a relatively new concept though it is well established in many countries.Study Aim: In this study, we aim to evaluate knowledge, attitude, and practice regarding pharmacovigilance and barriers to reporting adverse drug reactions (ADRs) among the general public in Saudi Arabia.Methods: This is a cross-sectional study that used a self-administered online questionnaire to assess knowledge, attitude, and practice of PV and ADRs. The study included only the adult population in Saudi Arabia. A scoring system was generated with a scale from 0 to 100, where 80% was set as a cut-off point, as any higher score resembled adequate knowledge, a positive attitude, and good practice. We used the Statistical Package for Social Sciences (SPSS) version 26 for performing the statistical analysis, where para-normal tests were used to associate scores with the socio-demographic characteristics of participants.Results: The study collected 1098 complete responses. The mean age (±SD) of participants was 37.9± 11.2 years. Females comprised 68.9% of the participants. The average knowledge score among participants was 37.8± 18.5, where only 4.3% of respondents had adequate knowledge. The average attitude score was 90.1± 19.2, where 83.4% had a positive attitude. The average practice score was 70.4± 18, and 34.5% of participants had good practice.Conclusion: The study found that the majority of participants had inadequate knowledge, a positive attitude, and poor practice. Individuals holding a master's degree or higher and those working in the healthcare sector had the highest knowledge scores, whereas the group aged 31 to 50 years old, participants from the Al Jawf region, participants who are married with children, holders of a master's degree or higher, and healthcare workers had the best attitude scores. Higher practice scores were seen among married individuals with children and those who work in the healthcare sector.Keywords: pharmacovigilance, adverse drug reactions, knowledge, attitude, practice, Saudi Arabia